Continuity of Urban Structures between Antiquity and Middle Ages in Croatia - Jurković, Miljenko (2006)
This presentation is an attempt of incorporation of Croatian art historic research into European research area through examination of the crucial issue of continuity of urban structures between antiquity and middle ages (4. ct. BC – 14. ct. AD) which is a basic binding point between Croatian cultural heritage and European cultural heritage as a whole. Contemporary scientific studies in Europe and in the world tend to omit from its contents the segment of urban development on the soil of modern day Croatia for multitude of reasons. The question of continuity of urban structures from the time of antiquity to modern days is still an object of intense scientific discussion in a European scientific community and Croatia has to position herself and its urban heritage inside of this discussion yet. Urbanity was firmly established in Croatia at the beginning 4. ct. BC when Greek civilization more seriously penetrated into the eastern Adriatic coast establishing its colonies – Issa (modern day town Vis on the isl and Vis) and Pharos (modern day Stari grad on the island Hvar) which was till then inhabited by autochthonous Illyrian peoples. Greek colonisation was followed by strong impact of romanization from 2. st. BC and finally Roman occupation in 1. ct. AD. Network of towns was further broadened in the period between 1– 6. ct. AD in accordance with principles of Roman organization of society and space which are still dominant and clearly observable in spatial organisation of modern day Croatian towns situated along the eastern Adriatic coast as well as in the landscape of the island and the coast. While this network of towns and cities belonged to an unified and almost “globalised” world of Roman Empire, period of Late Antiquity brought profound social and urban changes which varied according to circumstances which pervaded in different parts of Mediterranean basin. Although this period witnessed great migrations of peoples from the north and was often perceived in a scientific studies as a time of a decline of urbanity it is obvious that in a Croatian case there was no major break in the continuity of physical existence of towns. At the same time, processes of political, religious and social change inside towns and demographical change on the whole territory of Croatia (Slavic migration) led to the organic development of a new early medieval conception of urbanity which will soon become full grown medieval urban culture.